Levites, Priests, and Temple: Was the Chronicler Influenced by Ezekiel 40–48? - Amar, Itzhak (Vetus Testamentum, 2023)
This article examines whether Chronicles was influenced by Ezek 40–48—i.e., whether the book contains material not found in P or developed therefrom. To this end, it investigates the basis on which the Chronicler distinguishes priests from Levites, identifies those he deems responsible for guarding the Temple, elucidates his view of the Temple’s sanctity, and discusses whether he draws on one or several sources.